Structural, morphological, magnetic and dielectric characterization of nano-phased antimony doped manganese zinc ferrites. (May 2016) - Sridhar, Ch.S.L.N.; Lakshmi, Ch.S.; Govindraj, G.; Bangarraju, S.; Satyanarayana, L; Potukuchi, D.M.
Abstract: Nano-phased doped Mn–Zn ferrites, viz., Mn0.5− x /2 Zn0.5− x /2 Sb X Fe2 O4 for x =0 to 0.3 (in steps of 0.05) prepared by hydrothermal method are characterized by X-ray diffraction, Infrared and scanning electron microscopy. XRD and SEM infer the growth of nano-crystalline cubic and hematite (α-Fe2 O3 ) phase structures. IR reveals the ferrite phase abundance and metal ion replacement with dopant. Decreasing trend of lattice constant with dopant reflects the preferential replacement of Fe 3+ ions by Sb 5+ ion. Doping is found to cause for the decrease (i.e., 46–14 nm) of grain size. An overall trend of decreasing saturation magnetization is observed with doping. Low magnetization is attributed to the diamagnetic nature of dopant, abundance of hematite (α-Fe2 O3 ) phase, non-stoichiometry and low temperature (800 °C) sintering conditions. Increasing Yafet–Kittel angle reflects surface spin canting to pronounce lower Ms . Lower coercivity is observed for x ≤0.1, while a large Hc results for higher concentrations. High ac resistivity (~10 6  ohm-cm) and low dielectric loss factor (tan δ~10 −2 –10 −3 ) are witnessed. Resistivity is explained on the base of a transformation in the Metal Cation-to-Oxide anion bond configuration and blockade of conductivity path. Retarded hopping (between adjacent B-sites) of carriers across the grain boundaries is addressed. Relatively higher resistivity and low dielectric loss in Sbdoped Mn–Zn ferrite systems pronounce their utility in high frequency applications. Graphical abstract: Abstract : Highlights: Selection of metal oxides and mediating the reaction to extracting them in appropriate cationic state, as to dope the ferrites. Doping the ferromagnetic systems, viz., Mn-Zn ferrites at appropriate dopant concentration. Processing the doped ferrties grow them as Nanophased structures. Structural, morphological and spectroscopic characterization followed by determination of their field response. Optimization of the doped ferrite system for its enhanced performance in high frequency appliances.